2014
DOI: 10.3389/fnbeh.2014.00311
|View full text |Cite
|
Sign up to set email alerts
|

Chronic immobilization stress occludes in vivo cortical activation in an animal model of panic induced by carbon dioxide inhalation

Abstract: Breathing high concentrations of carbon dioxide (CO2) can trigger panic and anxiety in humans. CO2 inhalation has been hypothesized to activate neural systems similar to those underlying fear learning, especially those involving the amygdala. Amygdala activity is also upregulated by stress. Recently, however, a separate pathway has been proposed for interoceptive panic and anxiety signals, as patients exhibited CO2-inhalation induced panic responses despite bilateral lesions of the amygdala. This paradoxical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…There are several studies showed decreased cerebral blood volume (CBV) following chronic stress in animals and humans 1 , 11 13 . Prior exposure to chronic stress was reported to occlude strong activation of the somatosensory cortex by CO 2 inhalation using functional Magnetic Resonance Imaging (fMRI) and to exhibit a decreased hemodynamic response in the somatosensory cortex during hind paw electrical stimulation using optical intrinsic signal imaging 11 , 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several studies showed decreased cerebral blood volume (CBV) following chronic stress in animals and humans 1 , 11 13 . Prior exposure to chronic stress was reported to occlude strong activation of the somatosensory cortex by CO 2 inhalation using functional Magnetic Resonance Imaging (fMRI) and to exhibit a decreased hemodynamic response in the somatosensory cortex during hind paw electrical stimulation using optical intrinsic signal imaging 11 , 12 .…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies showed decreased cerebral blood volume (CBV) following chronic stress in animals and humans 1 , 11 13 . Prior exposure to chronic stress was reported to occlude strong activation of the somatosensory cortex by CO 2 inhalation using functional Magnetic Resonance Imaging (fMRI) and to exhibit a decreased hemodynamic response in the somatosensory cortex during hind paw electrical stimulation using optical intrinsic signal imaging 11 , 12 . According to the Poiseuille’s law of fluid dynamics, i.e., flow proportional to the fourth power of vessel radius, assuming that the blood pressure within the vessel is maintained, this would lead to ~23% reduction in cerebral blood flow, which could significantly impact the neurovascular regulation and brain metabolism 55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An ex vivo study showed that exposure to variable repeated stress and administration of corticosterone for 7 days lowered the responsiveness of the parenchymal arteriole in the amygdala to electrical stimulation (Longden et al, 2014 ). Stress also reduced the capillary diameters (Danielyan, 2008 ) and blood flow (Ohata et al, 1981 ; Lasbennes et al, 1986 ; Rahman et al, 2014 ) in several areas of the cortex in a rat acute or chronic immobilization stress model. In an electrophysiological study with brain slices, chronic stress decreased the function of inwardly rectifying K + channels in the endothelial smooth muscle cells of the amygdala, followed by decreased responsiveness of the intracerebral arterioles upon electric field stimulation (Longden et al, 2014 ).…”
Section: Introductionmentioning
confidence: 98%
“…Human functional MRI studies showed the increment of peripheral arterial blood pressure and perfusion signal changes in several brain areas when the subjects perceived mild stress (Carter et al, 2005 ; Wang et al, 2005 ). Compared to non-stressed animals, the stressed animals showed lower cerebral blood flow changes in the somatosensory cortex elicited by inhalation of high concentrations of CO 2 in a functional MRI study (Rahman et al, 2014 ). Because of the multi-faceted effects of chronic stress on hemodynamics, from modulator signaling to functional modulation, and the little direct evidence concerning the effect of chronic stress on the functional hemodynamic responses, the exact mechanisms responsible for the stress-evoked systematic changes remain elusive.…”
Section: Introductionmentioning
confidence: 99%